Educational reforms, a conflict public policies. - Rueda, Deisy Carolina; Moreno Farías, Bethy Edith; Bautista Pérez, Raúl Humberto (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of the article is to analyze the influence of educational reforms at a global level and their impact on public policies. An analytical-descriptive methodology based on documentary sources, review of books and articles in recognized databases and reports of international organizations on education in Latin America is used. It can be inferred that, during the last thirty years, state public policies significantly intervene in the educational field, ensuring adequate quality, expanding coverage, research, however, these are influenced by multilateral organizations, through underlying conditioning of the need of use of exogenous financial credits, a reality that leads to the progressive sacrifice of the real meaning and identity of education.